2016
DOI: 10.1089/dia.2015.0309
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Continuous Subcutaneous Insulin Infusion Therapy on Efficacy and Safety in a Cohort of Type 1 Diabetes Patients: A 3-Year Prospective Study

Abstract: Continuous subcutaneous insulin infusion achieved almost optimal glycemic control, reduced the number of hypoglycemic episodes without weight gain, and was well tolerated for the whole study period. Finally, this therapeutic approach was accompanied with lower daily insulin requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
1
0
3
Order By: Relevance
“…tied weight gain after insulin pump use to increased basal insulin dose and lower bolus to basal doses on insulin. Melidonis et al (20) showed a significant reduction in basal insulin doses of patients, especially after 2 years of insulin pump use. As we could only reach the total daily insulin doses of the patients, the role of basal insulin and bolus to basal ratio of insulin on this weight gain is difficult to interpret.…”
Section: Discussionmentioning
confidence: 98%
“…tied weight gain after insulin pump use to increased basal insulin dose and lower bolus to basal doses on insulin. Melidonis et al (20) showed a significant reduction in basal insulin doses of patients, especially after 2 years of insulin pump use. As we could only reach the total daily insulin doses of the patients, the role of basal insulin and bolus to basal ratio of insulin on this weight gain is difficult to interpret.…”
Section: Discussionmentioning
confidence: 98%
“…7. Дитячий вік (у США близько 80 % дітей, хворих на ЦД, використовують інсулінові помпи, в Європі -близько 70 %) [22][23][24].…”
Section: вступunclassified
“…Аналоги інсуліну ультракороткої дії є препаратами вибору для безперервного підшкірного введення при застосуванні в ІП [24,36]. Вважають, що використання аналогів інсуліну в ІП на високому рівні гарантує адекватний глікемічний контроль, низьку потребу в інсуліні, краще самопочуття пацієнта [37].…”
Section: обговоренняunclassified
“…Для улучшения качества лечения больных с СД1 уже более 40 лет используется метод постоянной подкожной инфузии инсулина (ППИИ). В ряде исследований продемонстрирована эффективность данного метода инсулинотерапии для достижения целевых значений гликемии и уменьшения частоты гипогликемических состояний [18,19]. Тем не менее, использование такого режима инсулинотерапии у женщин с СД1 во время беременности до сих пор является дискуссионным.…”
unclassified